Evaluation of Physical Attributes and Efficacy of Lip Balm Formulated with Okra Fruit Extract (Abelmoschus esculentus (L.) Moench Fructus) - Ana Yulyana; Alfioni Wulandari J.E; Saiful Bahri; Eko Mugiyanto (Faculty of Pharmacy Universitas Pancasila, 2024)
The okra fruit (A esculentus fructus) is renowned for its significant antioxidant properties, attributed to its rich content of bioactive compounds. Despite its high antioxidant activity, which has been extensively documented, its potential as a component in cosmetic formulations particularly lip balm preparation remains underutilized. This study seeks to address this gap by incorporating okra fruit extract into lip balm formulations and evaluating the resulting physical and functional attributes. Lip balm formulations were developed with three varying concentrations of Ethanol okra fruit extract: F1 (1%), F2 (3%), and F3 (5%). A series of comprehensive evaluations were conducted to assess the physical stability and performance of the lip balms, including organoleptic properties, homogeneity, pH, melting point, spreadability, and overall stability. Stability was monitored over a 28-day period at room temperature to simulate typical storage conditions. The antioxidant efficacy of the okra extract was quantified using the DPPH (1,1-diphenyl-2-picrylhydrazyl) assay, which yielded an IC50 value of 10.06 µg/ml, reflecting its potent free radical scavenging capacity. In comparison, the lip balm formulations demonstrated higher IC50 values, with Formulation I (FI) at 46.35 µg/ml, Formulation II (FII) at 40 µg/ml, and Formulation III (FIII) at 30.23 µg/ml, indicating a reduction in antioxidant activity in the formulated products compared to the pure extract.. The lip balm formulations exhibited a distinct okra aroma, smooth texture, and uniform color variations ranging from light brown (F1), brown (F2), to dark brown (F3). pH values ranged from 5.40 to 5.81, and melting points were between 49.6°C and 52.9°C, all within the acceptable range as per SNI 16-4769-1998 standards. ANOVA statistical analysis revealed no significant changes (p > 0.05) in melting point and spreadability over time. However, significant differences (p < 0.05) were noted in pH values, with further analysis indicating that formulations F2 and F3 differed significantly from F1 (p < 0.05). These results demonstrate that okra fruit extract not only enhances the antioxidant properties of lip balm but also maintains its stability and functionality, supporting its potential as a valuable ingredient in cosmetic formulations.